Implementasi Guru Pembimbing BK dalam Mengatasi Bulliying Siswa di SMP Negeri 59 Kota Bandung - Anita, Anita; Tini, Neng; Ratnawulan, Teti (Penerbit Widina, Widina Media Utama, 2025)
This study aims to examine the implementation of the role of Guidance and Counseling (BK) teachers in addressing bullying within SMP Negeri 59 in Bandung City. The phenomenon of bullying among students is increasingly prevalent and has become a serious concern due to its impacts on students' psychological and academic development. BK teachers play a strategic role in providing guidance, counseling, and effective interventions to reduce and prevent bullying behaviors. The research method employed is qualitative, with data collection techniques including interviews, observations, and documentation. The subjects of the study are BK teachers and students who have experienced bullying at SMP Negeri 59 in Bandung. The findings indicate that the implementation of BK programs in combating bullying has been carried out through various activities such as individual and group counseling sessions, character training, and anti-bullying socialization among students. However, there are challenges such as limited supporting facilities and time constraints faced by BK teachers. Furthermore, the success of the implementation heavily depends on the level of cooperation among BK teachers, students, and school staff. These findings suggest the need for enhancing the competence of BK teachers and strengthening collaboration with relevant stakeholders to improve the effectiveness of bullying prevention and intervention efforts. This research is expected to serve as a reference for developing more effective BK programs in addressing bullying in junior high schools.ABSTRAKPenelitian ini bertujuan untuk mengkaji implementasi peran Guru Pembimbing Bimbingan dan Konseling (BK) dalam mengatasi bullying di lingkungan SMP Negeri 59 Kota Bandung. Fenomena bullying di kalangan siswa semakin meningkat dan menjadi perhatian serius karena dampaknya terhadap perkembangan psikologis dan akademik siswa. Guru Pembimbing BK memiliki peran strategis dalam memberikan bimbingan, konseling, serta intervensi yang efektif guna mengurangi dan mencegah tindakan bullying. Metode penelitian yang digunakan adalah pendekatan kualitatif dengan teknik pengumpulan data melalui wawancara, observasi, dan dokumentasi. Subjek penelitian adalah Guru Pembimbing BK dan siswa yang mengalami bullying di SMP Negeri 59 Kota Bandung. Hasil penelitian menunjukkan bahwa implementasi program BK dalam mengatasi bullying telah dilakukan melalui berbagai kegiatan seperti sesi konseling individu dan kelompok, pelatihan karakter, serta sosialisasi anti-bullying kepada siswa. Namun, terdapat kendala seperti kurangnya fasilitas pendukung dan keterbatasan waktu yang dimiliki Guru BK. Selain itu, keberhasilan implementasi sangat bergantung pada tingkat kerjasama antara Guru BK, siswa, dan pihak sekolah. Temuan ini menyarankan perlunya peningkatan kompetensi Guru BK dan penguatan kerjasama dengan berbagai pihak terkait agar upaya pencegahan dan penanganan bullying dapat berjalan lebih optimal. Penelitian ini diharapkan dapat menjadi acuan dalam pengembangan program BK yang lebih efektif dalam mengatasi bullying di sekolah menengah pertama.